2017
DOI: 10.3897/zookeys.703.13385
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of North European Lumbricillus (Clitellata, Enchytraeidae)

Abstract: Lumbricillus is a genus of clitellate worms with about 80 described species that inhabit marine and limnic habitats. This study follows a recent analysis of the phylogeny of the genus based on 24 species of Lumbricillus collected mainly in Norway and Sweden. We provide the illustrated taxonomic descriptions of all these species and describe two of them as new; Lumbricillus latithecatus sp. n. and L. scandicus sp. n. Using the recent phylogeny, we informally divide Lumbricillus into five distinct morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The total number of cryptic species was 23: five in Tubifex tubifex , six in Limnodrilus hoffmeisteri , two in Enchytraeus buchholzi , two in Eiseniella tetraedra , two in Marionina argentea , three in Globulidrilus riparius and three in Nais communis . The sequence E3 (Enchytraeidae), identified in our previous work ( Vivien et al, 2015 ) as Lumbricillus rivalis Levinsen 1884, was attributed by Klinth, Rota & Erséus (2017) to Lumbricillus rutilus as part of a systematics study of the genus Lumbricillus . Therefore, we assigned the species L. rutilus to the lineage E3.…”
Section: Resultsmentioning
confidence: 93%
“…The total number of cryptic species was 23: five in Tubifex tubifex , six in Limnodrilus hoffmeisteri , two in Enchytraeus buchholzi , two in Eiseniella tetraedra , two in Marionina argentea , three in Globulidrilus riparius and three in Nais communis . The sequence E3 (Enchytraeidae), identified in our previous work ( Vivien et al, 2015 ) as Lumbricillus rivalis Levinsen 1884, was attributed by Klinth, Rota & Erséus (2017) to Lumbricillus rutilus as part of a systematics study of the genus Lumbricillus . Therefore, we assigned the species L. rutilus to the lineage E3.…”
Section: Resultsmentioning
confidence: 93%
“…We did find an immature specimen from the same locality, which could belong to the same species but has slightly fewer chaetae than the holotype. What immediately stands out with this new species is the short and stout spermatheca with its large ampulla, which, at first glance, seemed reminiscent of the spermathecae in Lumbricillus pagenstecheri (Ratzel 1869) and the pagenstecheri group (Timm 2005;Klinth et al 2017b). However, a closer examination revealed a lack of glands along the main part of the ectal duct (there is a ring of glands at the orifice only), therefore making it quite different; the species of the pagenstecheri group has both kinds of glands.…”
Section: Lumbricillus øRsted 1844mentioning
confidence: 94%
“…Lumbricillus Ørsted, 1844, p. 68 Pachydrilus (partim) Claparède, 1861, p. 75 Enchytraeus (partim) Ratzel, 1869, p. 856 Lumbricillus Nielsen & Christensen, 1959, p. 96 Lumbricillus Klinth et al 2017a, Klinth et al 2017b Lumbricillus sejongensis sp. nov. Holotype.…”
Section: Lumbricillus øRsted 1844mentioning
confidence: 99%
“…Fridericia dura (Enchytraeidae) is typically terrestrial (Dózsa-Farkas 2019), but was found outside its normal habitat in this study. The remaining enchytraeids and all naidids are normally restricted to aquatic or semi-aquatic habitats (Timm 2009;Schmelz & Collado 2010;Klinth et al 2017b), and they appear as a somewhat impoverished assemblage of the clitellates typical of streams, rivers, lakes and ponds in other parts of Northern Europe.…”
Section: Clitellates Of the Icelandic Springsmentioning
confidence: 99%
“…and Nais elinguis) are normally associated with marine, intertidal habitats. Lumbricillus arenarius is also known from a spring in Northern Svalbard (Klinth et al 2017b), and Nais elinguis is well known from both springs and coastal streams (e.g., Timm 2009), but the unidentified, possibly new species of Marionina was earlier collected only in marine habitats in Norway and Sweden (Erséus & Klinth, unpubl. ).…”
Section: Clitellates Of the Icelandic Springsmentioning
confidence: 99%